1971
DOI: 10.1017/s0043174500051158
|View full text |Cite
|
Sign up to set email alerts
|

Root Absorption and Translocation of Picloram by Oats and Soybeans

Abstract: The effects of time, concentration, pH, temperature, and metabolic inhibitors on 4-amino-3,5,6-trichloropicolinic acid (picloram) uptake from nutrient solution by oats (Avena sativaL. ‘Markton’) and soybeans (Glycine maxL. ‘Lee’) were studied. Oats and soybeans had similar absorption patterns of rapid initial uptake. However, total accumulation patterns markedly differed in that accumulation was concentration-dependent for oats but not for soybeans. Initial uptake by oats and soybean roots increased as solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

1973
1973
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
3
9
0
1
Order By: Relevance
“…These results strongly suggest that an energy relationship is involved in the uptake of picloram. Similar suggestions have been made earlier by other investigators for the uptake of picloram (Baur and Bovey 1970, Isensee et al 1971) and other growth regulators (Christie and Leopold 1965, Johnson and Bonner 1956, Vanden Born 1968. Subcellular distribution: -More than 95 "/o of the radioactivity in aqueous extracts of ^*C-picloram-treated excised plant segments was recovered in the soluble fraction (Table 2).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…These results strongly suggest that an energy relationship is involved in the uptake of picloram. Similar suggestions have been made earlier by other investigators for the uptake of picloram (Baur and Bovey 1970, Isensee et al 1971) and other growth regulators (Christie and Leopold 1965, Johnson and Bonner 1956, Vanden Born 1968. Subcellular distribution: -More than 95 "/o of the radioactivity in aqueous extracts of ^*C-picloram-treated excised plant segments was recovered in the soluble fraction (Table 2).…”
Section: Resultssupporting
confidence: 85%
“…These lines of evidence strongly suggest that there are both passive and active components involved in the uptake of picloram, possibly an initial entry by passive diffusion and then immediate involvement of an active metabolic component. A similar suggestion has been made by Isensee et al (1971) for picloram uptake by oat {Avena sativa L.) and soybean seedlings from nutrient solution. Metabolic processes also could have an indirect effect on uptake by influencing cytoplasmic viscosity and accumulation and binding of picloram in the tissue, thus altering the concentration gradient across the surface layers.…”
Section: Discussionsupporting
confidence: 78%
“…Arsenic might interfere with the biosynthetic pathway of PS, resulting in a low concentration of PS in the roots. It has been well established that arsenite reacts with the sulfhydryl groups of proteins in the roots (Speer 1973) causing a disruption to root function (Isensee et al . 1971; Orwick et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of roots, As might destroy the root structure, resulting in a decreased root length. It is known that arsenite reacts with sulfhydryl groups of proteins of roots (Speer 1973) causing disruption of the root function (Isensee et al 1971;Orwick et al 1976) and even cellular death. Carbonell-Barrachina et al (1995) found that the height of tomato plants decreased at 2, 5 and 10 mg As L −1 treatments.…”
Section: Shoot Height and Root Lengthmentioning
confidence: 99%